Rancang Bangun Doorlock Berbasis Sensor Fingerprint dan Sensor Touch Menggunakan Arduino Uno - Nurhidayat, Taufik; Haryawan, Agus (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2023)
The function of ATmega328p microcontroller as a microprocessor on instrument tool and control system. Microcontroller is non stand alone, it is should be connected with Bluetooth HC-05 module as a bluetooth sensor of microcontroller. In the other way, this system need to connect with a relay module as a on/off switch. Android smartphone is needed by user as a close device. Through sound command to Android smartphone, then Android smartphone is transmit a bluetooth signal to system of bluetooth module – microcontroller – relay module, so that system will cut off the electricity and lamp is can be switch on or off. According to constructed system, the lamp controller system is operate smoothly, but it is will be disruption in case smartphone is far away from Bluetooth HC-05 module operation range due to bluetooth connection will be loss automatically that is fifteen meters without barrier or eleven meters with barrier. The lamp controller system that utilized are Atmega328p as microcontroller and Android smartphone as a controller.